2023
DOI: 10.1007/s11240-023-02466-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of BrbHLH gene family and functional identification of the involvement of BcbHLH57 in abiotic stress in wucai (Brassica campestris L.)

Abstract: Wucai (Brassica campestris L. ssp. chinensis var. rosularis Tsen) is a subspecies of Brassica campestris, is a kind of cold-tolerant vegetable widely cultivated in the Yangtze-Huai River Basin of China. To breed new varieties of resistance to stress, it is necessary to study the tolerance of Resistance to different stresses. Transcriptomic data showed that exogenous application of 2, 4-epbrassinolide (EBR) significantly increased the bHLH genes expression in wucai at low temperature, and bHLH57 was up regulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…In a recent in vitro study utilizing Y2H screening, Masaru et al discovered that two MYC-type transcription factors, MYC67 and MYC70, can also interact with region C (amino acids 381–494) of ICE1. Additionally, they demonstrated that MYC67 and MYC70 can bind to the MYC cis-elements in the CBF3 promoter, potentially disrupting the interaction between ICE1 and the cis-elements, thereby negatively regulating cold tolerance. Intriguingly, these two studies suggest that dimerization is mediated by the ACT domain rather than the conventional HLH region. Consequently, further investigation is warranted to screen for potential interactions with the ACT domain.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%
“…In a recent in vitro study utilizing Y2H screening, Masaru et al discovered that two MYC-type transcription factors, MYC67 and MYC70, can also interact with region C (amino acids 381–494) of ICE1. Additionally, they demonstrated that MYC67 and MYC70 can bind to the MYC cis-elements in the CBF3 promoter, potentially disrupting the interaction between ICE1 and the cis-elements, thereby negatively regulating cold tolerance. Intriguingly, these two studies suggest that dimerization is mediated by the ACT domain rather than the conventional HLH region. Consequently, further investigation is warranted to screen for potential interactions with the ACT domain.…”
Section: The Function Of Bhlh Transcription Factors In Abiotic Stress...mentioning
confidence: 99%